Metal-mediated base pairs in parallel-stranded DNA - Müller, Jens (Beilstein Journal of Organic Chemistry, 2017)
In nucleic acid chemistry, metal-mediated base pairs represent a versatile method for the site-specific introduction of metal-based functionality. In metal-mediated base pairs, the hydrogen bonds between complementary nucleobases are replaced by coordinate bonds to one or two transition metal ions located in the helical core. In recent years, the concept of metal-mediated base pairing has found a significant extension by applying it to parallel-stranded DNA duplexes. The antiparallel-stranded orientation of the complementary strands as found in natural B-DNA double helices enforces a cisoid orientation of the glycosidic bonds. To enable the formation of metal-mediated base pairs preferring a transoid orientation of the glycosidic bonds, parallel-stranded duplexes have been investigated. In many cases, such as the well-established cytosine–Ag(I)–cytosine base pair, metal complex formation is more stabilizing in parallel-stranded DNA than in antiparallel-stranded DNA. This review presents an overview of all metal-mediated base pairs reported as yet in parallel-stranded DNA, compares them with their counterparts in regular DNA (where available), and explains the experimental conditions used to stabilize the respective parallel-stranded duplexes.
Keywords: DNA; metal-mediated base pairs; nucleic acids